Surface modification enhances the bulk proton conductivity of Prussian blue. Issue 33 (3rd April 2023) - Takahashi, Akira; Matsubayashi, Yasuhito; Sakurai, Atsushi; Sugiyama, Yutaka; Noda, Keiko; Kawamoto, Tohru
Abstract : Surface-modified Prussian blue shows 10 2 times higher bulk proton conductivity (0.018 S cm −1 ) than that of unmodified Prussian blue. Abstract : Surface-modified Prussian blue shows 10 2 times higher bulk proton conductivity (0.018 S cm −1 ) than that of unmodified Prussian blue. This enhancement is attributed to the monolayer adsorption of Na4 [Fe(CN)6 ] on the nanoparticle surface, which reduces the surface resistance. Surface modification is an effective strategy for improving bulk proton conductivity.